Democratic debete - "Miroff, Bruce" (New York, 2007)
n "The Democratic Debate", the facts of American politics are organised around the theme of democracy. Each chapter examines the tension between elite and popular models of democracy and the impact of that tension on institutions, processes and policy. The authors draw on the rich traditions of participatory democracy in America, challenging readers to examine their own beliefs about the nature of American democracy. The authors present a sympathetic picture of popular democrats from the anti-federalists to contemporary social movements but they also consider the other side of the debate - the argument for limiting popular participation.
Keywords: United States-Politics and government